Re-examining the impact of 63Co and 63Ni in the stellar environment - Kabir, Abdul; Nabi, Jameel-Un; Almujibah, Hamad; Anwaar, Izzah; Raza, Noor-Ul Ain (Frontiers in Physics, 2025)
The nuclear ground state properties of 63Co and 63Ni nuclei have been investigated within the framework of the relativistic mean field (RMF) approach. The RMF model with density-dependent meson-exchange (DD-ME2) interaction is used to calculate the potential energy curves (PECs) and nuclear ground state deformation parameters (β2) of 63Co and 63Ni. The blocking effects of the unpaired nucleon are considered using the equal filling approach for the odd-A system. Later, the β-decay properties, including the stellar weak rates and Gamow–Teller (GT) strength of 63Co and 63Ni, are studied using the proton-neutron quasiparticle random-phase approximation (pn-QRPA) model. The β2 values computed from the RMF model are employed in the pn-QRPA framework as an input parameter for the calculations of β-decay properties for 63Co and 63Ni. The stellar rates are compared with the projected shell model (PSM) results. For all densities, the pn-QRPA rates are found to be higher than the stellar rates computed via the PSM to a factor of 1.3 or more. The findings reported in the present investigation might be useful for simulating the late-stage stellar evolution of massive stars and the s-process of nucleosynthesis.